Two new species of Cossinae (Lepidoptera: Cossidae) from Sindh Province of Pakistan - Yakovlev, Roman V.; Saldaitis, Aidas (Zootaxa, 2016)
The Cossidae fauna of Pakistan is still poorly studied, with only a few species reported: Eremocossus foedus (Swinhoe, 1884), Aholcocerus ronkayorum Yakovlev, 2006, Cossulus griseatellus Yakovlev, 2006 and Phragmataecia gurkoi Yakovlev, 2007. The carpenter moths of Zeuzera Latreille, 1804 (Zeuzera sp. and Z. multistrigata Moore, 1881) have been reported in pest management publications from Pakistan (Mushtaque & Baloch 1981; Gul & Wali-ur-Rehman 1999; Viqar et al. 2005). The distribution of known cossid species of Pakistan is treated by Yakovlev (2011) without indicating specific localities. Mushtaque and Baloch (1981) report Z. multistrigata caterpillars feeding on the roots of Cannabis sativa L. (Cannabidaceae), which needs to be confirmed. Otherwise Zeuzera species have been observed only feeding on woody plants (Yakovlev 2012).